Extent of Mississippi River water in the Mississippi Bight and Louisiana Shelf based on water isotopes. (15th October 2019) - Sanial, Virginie; Shiller, Alan M.; Joung, DongJoo; Ho, Peng
Abstract: The northern Gulf of Mexico is a complex and very productive coastal river-dominated system that receives freshwater from numerous rivers including the Mississippi River. The dynamics of coastal ecosystems in the northern Gulf of Mexico are greatly influenced by the freshwater discharge but also by the high nutrient loads carried by the Mississippi River that lead to the seasonal development of one of the largest coastal hypoxic areas. Constraining the origin and fate of the freshwater inputs in the northern Gulf of Mexico will help increase understanding the physical and biogeochemical processes occurring in this region. Here, we focus on investigating the extent of the Mississippi River plume on both sides of the Mississippi River Delta: to the east in the Mississippi Bight, and to the west over the Louisiana Shelf. We determined the water isotopic signature (δ 18 O and δD) along with salinity of the different river plumes and performed a river mixing model on the coastal waters. Our findings provide useful information to better understand the functioning of the northern Gulf of Mexico ecosystem. In particular, the development of hypoxia is often attributed to the nutrient load of the Mississippi River, yet the Mississippi River seemed to have a limited influence on the Mississippi Bight. That is, the dominant source of freshwater in the Bight was supplied by local Mississippi/Alabama rivers. Furthermore, the water isotope mixing model showed that the source of freshwater to the Louisiana Shelf was dominated by the Atchafalaya River in summer, and by the Mississippi River during non-summer seasons. This pattern is consistent with the general shelf circulation that reverses in summer, but could not have been shown solely by the use of salinity.